2021
DOI: 10.1111/adb.13061
|View full text |Cite
|
Sign up to set email alerts
|

Brain imaging of cannabinoid type I (CB1) receptors in women with cannabis use disorder and male and female healthy controls

Abstract: Cannabis effects are predominantly mediated by pharmacological actions on cannabinoid type 1 (CB1) receptors. Prior positron emission tomography (PET) studies in individuals who use cannabis included almost exclusively males. PET studies in females are needed because there are sex differences in cannabis effects, progression to cannabis use disorder (CUD), and withdrawal symptom severity. Females with CUD (N = 10) completed two double‐blind cannabis smoking sessions (Session 1: placebo; Session 2: active), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 55 publications
1
16
2
1
Order By: Relevance
“…In a more recent study from the same researchers, the results showed lower [ 11 C]CURB binding among a group (n = 14) of young chronic cannabis users (23 ± 5 years of age) compared to healthy controls during early abstinence throughout the whole neocortex and striatum, Amy, Hipp, thalamus and cerebellum [108]. Another study using [ 11 C]OMAR studied the changes in CB1R availability in women with CUD (n = 10), who displayed significantly lower V T than healthy female controls (n = 10) in the Hipp, Amy, cingulate, and insula, similar to previous studies in men [109]. Interestingly, a recent review on psychiatric disorders also evaluated PET studies in CUD and AUD [122].…”
Section: Neuroimaging Of Ecs Componentssupporting
confidence: 56%
“…In a more recent study from the same researchers, the results showed lower [ 11 C]CURB binding among a group (n = 14) of young chronic cannabis users (23 ± 5 years of age) compared to healthy controls during early abstinence throughout the whole neocortex and striatum, Amy, Hipp, thalamus and cerebellum [108]. Another study using [ 11 C]OMAR studied the changes in CB1R availability in women with CUD (n = 10), who displayed significantly lower V T than healthy female controls (n = 10) in the Hipp, Amy, cingulate, and insula, similar to previous studies in men [109]. Interestingly, a recent review on psychiatric disorders also evaluated PET studies in CUD and AUD [122].…”
Section: Neuroimaging Of Ecs Componentssupporting
confidence: 56%
“…Yet, although we observed significant increases in ratings of irritability, misery and anxiety during abstinence, celecoxib did not reduce these symptoms. Although we saw effects of celecoxib on sleep ratings and cannabis craving, suggesting it had centrally mediated effects, other adaptations in the endogenous cannabinoid system associated with daily cannabis, 42 including CB1 downregulation 43–46 and reduced FAAH activity, 42,47 may have mitigated the impact of COX‐2 inhibition on cannabis withdrawal symptoms. If repeated cannabis exposure increases COX‐2 activity but reduces FAAH activity, a net change in circulating eCBs and subsequent behaviour might not manifest, at least at this dose of celecoxib.…”
Section: Discussionmentioning
confidence: 85%
“…50 If, in fact, repeated cannabis use alters eCB levels, then it may be that a longer period of abstinence is needed to reverse cannabis-induced compensatory decreases in circulating levels of eCBs. CB1 receptors typically normalize after $2-14 days of abstinence [43][44][45][46] so 4 days of abstinence may not have been sufficient to reverse the effects of daily cannabis use on eCB levels.…”
Section: Discussionmentioning
confidence: 99%
“…One possible explanation for the relationship between cannabis use and corpulence is that such frequent use may downregulate cannabinoid receptor 1 (CB1)—which regulates appetite and body weight, thereby reducing energy storage and increasing metabolic rates (Clark et al 2018 ; Spindle et al 2021 ). In two preclinical studies, CB1 antagonists and peripherally restricted CB1 antagonists (i.e., with no effect on the central nervous system) showed some efficacy on obesity and metabolic syndrome (O’Sullivan et al 2021 ; Lopez Trinidad et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%